Frightening light - "Arnold. Nick" (Scholastic London, 2009)
This is science with the squishy bits left in! What stops your eyeballs from falling out? Why can dead bodies make ghostly glowing lights? How can a laser beam sizzle human flesh? Get the awful answers in "Frightening Light"!